PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, DAN KOMISARIS INDEPENDEN TERHADAP PENGHINDARAN PAJAK - Huda, Fathin Kamalia Zulfa; Kiryanto, Kiryanto (Program Studi Akuntansi Universitas Flores, 2026)
This inquiry concentrates on assessing how profitability, corporate scale, and the share of independent commissioners contribute to shaping tax avoidance among consumer staples manufacturing firms listed on the Indonesia Stock Exchange (IDX) during 2021–2023. The rationale for this investigation stems from the persistent pattern of tax avoidance in Indonesia. Employing a quantitative framework, the study adopts a purposive sampling method, selecting 44 firms that yield 132 firm-year data points. The research relies on secondary evidence derived from annual reports and publicly released financial statements available at the IDX. Profitability—captured through Return on Assets (ROA)—firm size—proxied by the natural logarithm of total assets—and the proportion of independent commissioners on the board serve as explanatory variables. Tax avoidance, the dependent construct, is operationalized via the Cash Effective Tax Rate (CETR). The statistical procedure involves multiple linear regression conducted with SPSS, preceded by classical assumption diagnostics to ensure robustness of the model. The empirical findings indicate a significant and inverse association between profitability and tax avoidance. In contrast, both firm size and independent commissioners’ proportion show no significant influence. Nevertheless, when jointly examined, the three predictors collectively exert an effect on tax avoidance. These results imply that companies with stronger profitability are more inclined toward tax compliance, whereas firm size and the share of independent commissioners have yet to demonstrate tangible effectiveness in curbing tax avoidance practices. The study contributes to the accounting literature and provides practical insights for policymakers and corporate actors seeking to strengthen tax compliance.